The Ultimate Self Care Book : Improve your wellbeing, build resilience and confidence, master mindfulness - Seeger, Clara; Forsyth, Patrick; Michelli, Dena; Evans-Howe, Stephen (London : Teach Yourself, 2020)
If you want to be the best, you have to have the right skillset. From confidence and assertiveness to managing stress and mindfulness, 'The Ultimate Self Care Book' is a dynamic collection of tools, techniques, and strategies for success. Discover the main themes and key ideas, and bring it all together with practical exercises. This is your complete course in wellbeing at work.
Includes bibliographical references.
Keywords: Psychology, Industrial; Well-being.; Mindfulness (Psychology); Stress management; Self-actualization (Psychology); Psychology